Predictive Values of Neutrophil to Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio for Systemic Inflammatory Response Syndrome after Percutaneous Nephrolithotomy - Mehrdad Mohammadi Sichani (Urology Research Center, 2021)
Introduction: Percutaneous nephrolithotomy (PNL) is widely used for kidney stones. One of the complications of PNL is Systemic inflammatory response syndrome (SIRS), which is of great importance. Here we wanted to estimate the effectiveness of neutrophil to lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) in predicting SIRS following PNL. Methods: This study is prospective observational work done in 2018-2019 in Isfahan, Iran, on patients diagnosed with kidney stones that were candidates of PNL. We collected patient demographic data, including gender, age, and size of kidney stones. Information about the operation duration, procedures, and laboratory data were collected before and after the procedures. All data were compared between patients with or without SIRS after PNL. Results: In the present study, 152 candidates for PNL entered the research. The average age of the patients was 52.1± 13.4 years. In this study, 95 patients (62.5%) were male, and 57 (37.5%) were female. The average stone size was 29.4± 5.3 mm. Based on our data; 26 patients (17.1%) had sepsis after the procedure. There was only a significant difference between groups of patients regarding primary stone composition in the way that 92.3% of cases with sepsis had two stone compositions while 44.4% of other patients had two stone compositions and 50% had one stone composition (P-value<0.001). We found that patients that had sepsis after PNL had significantly higher operation duration (P-value=0.044) and significantly higher packed cell transfusion (30.8%) compared to other patients (4%) (P-value<0.001). The NLR below 72.2 could predict sepsis after PNL with 80.5% sensitivity and 33.3% specificity. Furthermore, the PLR below 63.3 could predict sepsis after PNL with 90.9% sensitivity and 5.3% specificity. Conclusion: Elevated NLR and PLR are associated with increased frequencies of SIRS after PNL. These data could be used effectively in predicting SIRS in these patients.